Consumer Behavior and Marketing Action - Assael H. (Henry) (Boston: PWS-KENT Publishing Company, 1992)
This fourth edition of "Consumer Behavior and Marketing Action" is the most extensive revision to date. As with the previous three editions, this edition ties together the conceptual foundations of consumer behavior and an applications orientation. The simple premise is that if consumer needs are to drive marketing strategies, a better understanding of these needs should be the foundation for strategy development.
(NP(B/12772s
+Photos
Keywords: consumer -- marketing -- communications